A case report as a novel technique in the management of liver injury combined with common hepatic duct avulsion in pediatrics. Issue 2 (April 2018) - Gouda, Samir; Al-Sayed Daboos, Mohammad
Abstract : Liver trauma in pediatrics one of the challenged condition especially if associated with biliary injury because of difficulty in control the hepatic bleeding and repair of biliary duct injury. Life saving and try to decrease postoperative morbidity and mortality. Child 10 years old with blunt abdominal trauma submitted for laparotomy with control of hepatic bleeding and repair of avulsed hepatic duct with stenting. Uneventful postoperative course improvement of child with monthly follow-up for later on removal of stent. Repair of injured biliary ducts with stenting is the best method for management.